Innovative Qurbani Marketing for Greater Social Impact: Evidence From Indonesia - Indah Piliyanti (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study aims to analyze the landscape of marketing innovations for qurbani by the BAZNAS (Badan Amil Zakat Nasional) and LAZ (Lembaga Amil Zakat) in Indonesia during the 2021–2025 period, including a comparison of segmentation, targeting, positioning, and 4P marketing mix strategies, as well as an evaluation of their social impact through the perspective of maqasid al-shariah. This research employs a qualitative comparative case study approach involving 67 Islamic philanthropic institutions consisting of 34 provincial BAZNAS offices and 33 national LAZ. Data were collected through document analysis of annual reports, official websites, institutional publications, regulations, audited financial reports, and academic literature. The findings reveal that qurbani marketing innovations are concentrated in product development, digital promotion, distribution systems, and strategic partnerships. LAZ demonstrates greater adaptability in product innovation, strategic flexibility, and transparency-based promotion, while BAZNAS excels in institutional legitimacy, national coordination, and distribution reach. Programs such as Superqurban, digital qurbani tracking, and livestock empowerment indicate that qurbani management has transformed into a sustainable socio-economic ecosystem emphasizing social impact, transparency, and distributive justice. The study finds an integrative model of qurbani marketing that links marketing strategies, sharia values, and institutional accountability. The findings is a prove that from religious tradition of qurbani transforms to innovation of Islamic philanthropic organization in Indonesia.